Are uroflowmetry and post - void residual urine tests necessary in children with primary nocturnal enuresis? - Shang-Jen Chang; Stephen Shei-Dei Yang (International Brazilian Journal of Urology)
ABSTRACT Objectives: To examine the benefits of repetitive uroflowmetry and post void residual urine (PVR) tests in children with primary nocturnal enuresis (PNE). Material and methods: Children aged ≥6 years with PNE who visited our clinics for management of enuresis were included for study. Patients were requested to complete a questionnaire including baseline characteristics and Dysfunctional Voiding Symptom Score (DVSS), 2-day bladder diary, and Rome III criteria for constipation. Two uroflowmetry and PVR tests were requested. Children with congenital or neurogenic genitourinary tract disorders were excluded. All children underwent urotherapy and desmopressin combined with anticholinergics or laxatives if indicated. The definition of abnormal flow patterns (≥1 abnormal), elevated PVR (≥1 abnormal), small maximal voided volume (MVV), nocturnal polyuria (NP) and response to treatment complied with the ICCS standardization document. Kaplan-Meier survival analysis and Cox proportional-hazards regression tests were used to evaluate the predictors of response. Results: In total, 100 children aged 8.5±2.3 years were enrolled for study (M: F=66:34) with 7.3±7.4 months of follow-up. Poor correlation was observed between DVSS/small MVV and PVR (p>0.05). Univariate analysis revealed that elevated PVR is associated with significantly less hazard of complete response to medical treatment (HR: 0.52, p=0.03), while not significantly associated with abnormal flow patterns, NP, constipation or small MVV. Multivariate analysis revealed that only elevated PVR (HR 0.30, 95% CI 0.12-0.80) and NP (HR 2.8, 95% CI 1.10-7.28) were significant predictors for complete response. Conclusions: In managing pediatric enuresis, elevated PVR is a significant predictor for lower chance of complete response to treatment whether they had high DVSS or not.